ANALYSIS OF THE PERCEPTUAL OF BODY FAT OBTAINED BY DIFFERENT METHODS OF ASSESSMENT (ANTHROPOMETRY AND OF HYDROSTATIC WEIGHING) (Fiep Bulletin - online, 2014)
This  study was aimed at verifying if there is difference among the values of perceptual of body fat (%BF) obtained by the methods anthropometric [through the techniques of skinfolds (A-SF+C) and circumferences - generalized equations (A-GC) and specific (A-SC)] and of hydrostatic weighing (HW). Physically active university students were assessed, divided into 2 groups: 23 men (MG) (age of 21,90±2,28, stature of 176,11±6,26cm, 73,98±8,54kg), 13 women (GF) (age  of 20,92±1,70, stature of 162,47±3,61cm, 57,22±6,96kg). According to the results obtained all the values of %GC for the methods investigated differed statistically (HW vs A-GC p
Keywords: perceptual of body fat; assessment methods; men and women